1966
DOI: 10.1139/m66-085
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Studies on the Mechanism of Action of Sparsomycin

Abstract: A primary site of sparsomycin attack in Escherichia coli appears to be inhibition of synthesis of protein, which occurs at concentrations of sparsomycin that do not affect DNA or RNA synthesis. Sparsomycin interferes with the normal excretion of amino acids by E. coli. Some cross-resistance was observed between a culture resistant to sparsomycin and cultures resistant to other inhibitors of protein synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…(7? )-2-(Difluoromethyl)dehydroornithine Hydrochloride (10). A mixture of 9a (1.2 g), acetic acid (10 mL), and concentrated hydrochloric acid (30 mL) was heated at reflux temperature for 42 h. After concentration in vacuo, the residue was taken up with water (10 mL).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(7? )-2-(Difluoromethyl)dehydroornithine Hydrochloride (10). A mixture of 9a (1.2 g), acetic acid (10 mL), and concentrated hydrochloric acid (30 mL) was heated at reflux temperature for 42 h. After concentration in vacuo, the residue was taken up with water (10 mL).…”
Section: Methodsmentioning
confidence: 99%
“…These were transformed into 17 and 14 via a four-step sequence involving (a) phthaloyation of the amine function; (b) allylic bromination of the methyl group; (c) Gabriel reaction; and (d) hydrolytic cleavage of the protective groups. (E)-a-(Difluoromethyl)dehydroornithine (10) and -putrescine (7) were prepared from ethyl ferf-butyl 2-(difluoromethyl)-2-(2-propenyl)malonate and di-tert-butyl 2-(difluoromethyl)-2-(2-propenyl)malonate, respectively, via a sequence similar to that reported previously for the synthesis of the saturated analogues. Compounds 17,14,10, and 7 proved to be much more potent enzyme-activated irreversible inhibitors of ODC than the corresponding saturated analogues.…”
Section: Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated in 1962 from Streptomyces sparsogenes , , sparsomycin was quickly identified as a universal translation inhibitor with activity against a variety of eukaryotic and prokaryotic cells. The structure of the sparsomycin–ribosome complex was solved and demonstrated that it binds simultaneously with the P-site tRNA mimic (3′-CCA-Phe) (Figure ). It also demonstrated a π-stacking interaction with A2637 and prohibits the movement of A2637, a critical residue facilitating the movement of tRNAs between the A- and P-site.…”
Section: Ribosomal P-site Inhibitors: the Universal Antibioticsmentioning
confidence: 99%